Financial Innovation and the Transactions Demand for Cash - Álvarez, Fernando; Lippi, Francesco (Econometrica, 2009)
We document cash management patterns for households that are at odds with the predictions of deterministic inventory models that abstract from pre-cautionary motives. We extend the Baumol-Tobin cash inventory model to a dynamic environment that allows for the possibility of withdrawing cash at random times at a low cost. This modification introduces a precautionary motive for holding cash and naturally captures developments in withdrawal technology, such as the increasing diffusion of bank branches and ATM termi-nals. We characterize the solution of the model and show that qualitatively it is able to reproduce the empirical patterns. Estimating the structural pa-rameters we show that the model quantitatively accounts for key features of the data. The estimates are used to quantify the expenditure and interest rate elasticity of money demand, the impact of financial innovation on money demand, the welfare cost of inflation, the gains of disinflation and the benefit of ATM ownership.